Method for preparing synthetic quartz sand by sol-gel method
Through the sol-gel method of acid-base catalysis and silicon source drop acceleration regulation, combined with the solvent recovery technology of distillation and condensation, the long gel cycle, high sintering temperature and solvent in the preparation process of high-purity synthetic quartz sand in the existing technology is solved. The problem of inconvenience in recycling has achieved an efficient, low energy consumption and environmentally friendly production process.
Patent Information
- Application Number
- CN202411725912.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-14
AI Technical Summary
The existing sol-gel method for preparing high-purity synthetic quartz sand has problems such as long gel cycle, low efficiency, high sintering temperature, high energy consumption and inconvenient solvent recovery, resulting in low production efficiency and environmental pollution.
Accurately control the gelling time through acid and alkali catalysis to reduce production cycle and energy consumption; regulate the silt source drop acceleration to control the size and uniformity of silica particles and reduce the sintering temperature; recover through distillation and condensation during the drying of wet gel Solvent, achieve green production.
The gel cycle is shortened, the product purity is improved, the energy consumption is reduced, and the solvent is recovered, which improves production efficiency and reduces environmental pollution.
Smart Images

Figure CN119430199A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of synthetic quartz sand preparation, and in particular to a method for preparing synthetic quartz sand by a sol-gel process. Background Art
[0002] High-purity quartz sand is the key raw material for producing high-purity quartz glass tubes, quartz ingots, and quartz crucibles. The quality of high-purity quartz sand determines the quality of quartz tubes, quartz crucibles and other quartz products. Due to their excellent physical and chemical properties, high-end quartz products are widely used in semiconductors, photovoltaics, high-end light sources, optical communications, and aerospace. With the development of high-tech industries, the demand for high-purity quartz sand has increased rapidly, and the quality requirements are getting higher and higher.
[0003] At present, high-purity quartz sand is mainly obtained by purifying natural quartz ore, and its production capacity is closely related to high-quality ore sources. The natural high-purity quartz raw materials for preparing high-purity quartz sand mainly include crystal, granite pegmatite, vein quartz, etc. The finished quartz sand is obtained after the raw ore is crushed, magnetically separated, floated, acid-leached, dried, and roasted. Its advantage is that the process is simple. With the gradual depletion of natural crystals and high-quality quartz veins worldwide, the price of high-purity quartz sand has continued to rise, and the process of chemically synthesized quartz sand has gradually received attention and research.
[0004] With the increasing demand for semiconductor, photovoltaic and optical technologies, the requirements for high-purity quartz sand are constantly increasing. The purity of natural quartz ore is difficult to further improve due to the influence of its associated substances, growth environment and purification technology. Therefore, the preparation of quartz sand by chemical synthesis process is considered to be one of the main directions of future technological development. Especially as the line width of semiconductor chips becomes narrower and narrower, ordinary natural quartz materials can no longer meet the requirements of high-end production processes, and synthetic quartz has become an important component in the etching process of semiconductor chips below 10nm process.
[0005] At present, the technical routes for high-purity synthetic quartz sand mainly include gas phase synthesis method, chemical precipitation method, sol-gel method, liquid phase hydrolysis method of silicon tetrachloride, etc. These methods all use silicon-containing elements as precursors, such as hydrolysis reaction of silicon tetrachloride or organosilane tetramethoxysilane, tetraethoxysilane, etc., or react silicate with acid to prepare silicon dioxide powder, and then sinter under certain temperature or atmosphere conditions to prepare high-purity synthetic quartz sand.
[0006] Patent CN 110255570B discloses a method for preparing high-purity synthetic sand, which uses a 40% water glass solution as a silicon source, and obtains a silicic acid aqueous solution through dealkalization. The silicic acid aqueous solution is kept at room temperature or heated to gel, and then freeze-dried to obtain silicon dioxide particles, which are kept at 1210°C for 10 hours to obtain high-purity quartz sand particles. The quartz sand synthesized by this method has a purity of only 4N. According to the analysis of its synthesis method, the reason for its low purity is that water glass is used as the raw material, in which Na + It is difficult to remove; and this method requires a long time for gelation, high sintering temperature, long insulation time, and low efficiency.
[0007] Patent CN 116375040A discloses a method for preparing synthetic quartz sand by sol-gel method, using organic silicate as silicon source, ultrapure electronic grade C1-C2 alcohol and ultrapure water as solvent, and electronic grade ammonia water as catalyst to prepare silica sol by two-step hydrolysis, and then keep warm at 1300-1350℃ for 4-4.5h to obtain high-purity synthetic quartz sand. This method takes a total of 16-24h for the two-step hydrolysis, which is a long time; at the same time, it is not clear how to separate silica from the sol, the required sintering temperature is high, and the solvent recovery problem is not considered.
[0008] Although the existing chemical synthesis method can produce high-purity quartz sand, there are some problems in the process. First, the currently disclosed method of preparing synthetic quartz sand by sol-gel method generally uses acid or alkali as catalyst alone, which makes the gelation time difficult to control, the preparation cycle is long and the efficiency is low. At the same time, it may cause the particle size and morphology of silicon dioxide to be difficult to control, thereby affecting the subsequent sintering performance. Secondly, the existing disclosed method usually needs to be sintered at a higher temperature or under certain atmosphere conditions, which not only increases energy consumption, but also has higher requirements on equipment materials. Finally, the existing methods do not consider the problem of solvent recovery, which not only increases production costs, but also may pollute the environment. Summary of the invention
[0009] In view of the deficiencies in the prior art, the present invention provides a method for preparing synthetic quartz sand by a sol-gel method, wherein the gelation time is precisely controlled by two-step acid-base catalysis, the production cycle is reduced, and the production efficiency is improved; at the same time, the silicon dioxide particle size and uniformity are controlled by controlling the silicon source droplet addition velocity, thereby greatly reducing the sintering temperature of the synthetic quartz sand; and the solvent is recycled by distillation when the wet gel is dried, thereby reducing the production cost and the pollution to the environment.
[0010] In order to solve the above technical problems, the present invention provides a method for preparing synthetic quartz sand by a sol-gel method, comprising the following steps:
[0011] S1, mixing silicon alkoxide and alcohol solvent, stirring at 40-60°C for 30-60 minutes to form a homogeneous solution, recorded as L1;
[0012] S2, mixing the acidic catalyst, the alcohol solvent and the ultrapure water to form a mixed solution, recorded as L2;
[0013] S3, at 40-60°C, add L1 solution to L2 solution, and then continue stirring and hydrolyzing for 2-4 hours to obtain SiO2 sol;
[0014] S4, under stirring, adding ammonia water dropwise to the SiO2 sol until the pH value is 5-10, and placing the sol in a vacuum drying oven at 60-80° C. to obtain a wet gel;
[0015] S5, drying the wet gel, and then placing it in a sintering furnace for sintering to obtain high-purity synthetic quartz sand.
[0016] The present invention firstly dissolves the silicon source in a solvent, performs a hydrolysis reaction under the catalytic action of an acidic catalyst to obtain a SiO2 sol, then adds an alkaline catalyst to promote the rapid polymerization of SiO2 particles, and accurately controls the gelation time by adjusting the pH, thereby greatly reducing the gelation cycle and improving the reaction efficiency.
[0017] Furthermore, in S5, the sintering treatment conditions are: heating from room temperature to 300°C and keeping it for 10-30 minutes, heating to 500°C and keeping it for 30-60 minutes, and continuing to heat to 900-1100°C and keeping it for 240-300 minutes.
[0018] The present invention controls the size and uniformity of silicon dioxide particles by regulating the dropping speed of L1 solution. The generated silicon dioxide particles have a large specific surface area and high activity. Therefore, high-purity synthetic quartz sand with good transparency can be obtained at a relatively low sintering temperature (900-1000°C), which greatly reduces energy consumption and avoids the problem of material selection for high-temperature sintering equipment.
[0019] Furthermore, in S5, the drying process is carried out by oil bath heating drying, and the temperature of the drying process is 120-150°C.
[0020] Furthermore, in S5, during the drying process, a condensation device is used to recover the solvent, wherein the solvent includes an alcohol solvent and ultrapure water, and the ratio of the alcohol solvent to the ultrapure water in the solvent is analyzed, and the ratio is adjusted and then recycled to step S2. Recovering the solvent by distillation and condensation not only reduces production costs, but also reduces the environmental pollution of the solvent, thereby achieving green production.
[0021] Furthermore, the volume ratio of the L1 solution to the L2 solution is 5:1;
[0022] In S3, the dropping rate is 0.5 mL / min-10 mL / min; and / or the dropping time t is 20 min≤t≤180 min. The size of the generated SiO2 particles is regulated by adjusting the dropping rate: when the dropping rate is faster, the formed SiO2 particles are smaller; when the dropping rate is slower, the formed SiO2 particles are larger; this method is used to control the particle size and uniformity of silica.
[0023] Furthermore, in S4, the concentration of the ammonia water is 0.5 mol / L, the ammonia water is electronic grade ammonia water, and the total amount of metal impurities is less than 10 ppb;
[0024] And / or, the dripping rate of the ammonia water is ≤0.5 mL / min. The dripping rate of the ammonia water is controlled to avoid excessively fast dripping rate to produce precipitation.
[0025] Further, in S1, the silicon alkoxide is ethyl orthosilicate and / or methyl orthosilicate;
[0026] And / or, the molar ratio of the silicon alkoxide to the alcohol solvent is 1:(10-50).
[0027] Further, in S2, the acidic catalyst is one or more of electronic grade hydrochloric acid, nitric acid, and sulfuric acid;
[0028] And / or, the resistivity of the ultrapure water at 25° C. is greater than 18 MΩ·cm;
[0029] And / or, the molar ratio of the acidic catalyst, the alcohol solvent and the ultrapure water is 1:(4-10):(10-20).
[0030] Furthermore, in S1 and S2, the alcohol solvent is anhydrous ethanol or anhydrous methanol.
[0031] Furthermore, before S1, a distillation step of the silicon alkoxide is also included.
[0032] Beneficial effects of the present invention:
[0033] The present invention adopts the sol-gel method to prepare high-purity synthetic quartz sand, which has the advantages of short gel cycle, high product purity, low energy consumption, and solvent recovery. Specifically:
[0034] The present invention obtains SiO2 sol by catalyzing the hydrolysis of silicon source with an acidic catalyst, promotes the rapid polymerization of SiO2 particles by adding an alkaline catalyst, and adjusts the pH to accurately control the gelation time, thereby greatly reducing the gelation period and improving the reaction efficiency.
[0035] The present invention controls the size and uniformity of silicon dioxide particles by regulating the dropping speed of the silicon source solution. The generated silicon dioxide particles have a large specific surface area and high activity, so that high-purity synthetic quartz sand with good transparency can be obtained at a relatively low sintering temperature (900-1000°C), which greatly reduces energy consumption and avoids the problem of material selection for high-temperature sintering equipment.
[0036] The present invention recovers the solvent by distillation and condensation during the drying process of the wet gel, which not only reduces the production cost, but also reduces the pollution of the solvent to the environment, thereby realizing green production. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 This is a process flow chart of preparing high-purity synthetic quartz sand by the sol-gel method of the present invention;
[0039] Figure 2 It is a schematic diagram of the solvent recovery process in preparing high-purity synthetic quartz sand by the sol-gel method of the present invention;
[0040] Figure 3 is a distribution diagram of sol particle size in Example 1 of the present invention;
[0041] Figure 4 This is a photo of synthetic quartz sand in Example 1 of the present invention;
[0042] Figure 5 is a distribution diagram of sol particle size in Example 2 of the present invention;
[0043] Figure 6 This is a photo of synthetic quartz sand in Example 2 of the present invention;
[0044] Figure 7 This is a photo of synthetic quartz sand in Comparative Example 1 of the present invention;
[0045] Figure 8 This is a photo of synthetic quartz sand in Comparative Example 2 of the present invention;
[0046] Fig. 9 This is a photo of the synthetic quartz sand in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0047] The technical solution of the present invention will be described clearly and completely below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] The present invention provides a method for preparing synthetic quartz sand by a sol-gel method, the flow chart of which is shown in FIG. Figure 1 As shown, the following steps are included:
[0049] S1, mixing silicon alkoxide and alcohol solvent, stirring at 40-60°C for 30-60 minutes to form a homogeneous solution, recorded as L1;
[0050] S2, mixing the acidic catalyst, the alcohol solvent and the ultrapure water to form a mixed solution, recorded as L2;
[0051] S3, at 40-60°C, add L1 solution to L2 solution, then keep the temperature constant and continue stirring and hydrolyzing for 2-4h to obtain SiO2 sol;
[0052] S4, under stirring, adding ammonia water dropwise to the SiO2 sol until the pH value is 5-10, and placing the sol in a vacuum drying oven at 60-80° C. to obtain a wet gel;
[0053] S5, drying the wet gel, and placing it in a sintering furnace for sintering heat treatment to obtain high-purity synthetic quartz sand;
[0054] The drying process adopts oil bath heating drying, and the drying process temperature is 120-150°C; the sintering process conditions are: heating from room temperature to 300°C and keeping warm for 10-30 minutes, heating to 500°C and keeping warm for 30-60 minutes, and continuing to heat to 900-1100°C and keeping warm for 240-300 minutes.
[0055] As a preferred embodiment, during the drying process, a condensing device is used to recover the solvent. Figure 2 As shown, the solvent includes an alcohol solvent and ultrapure water, and the ratio of the alcohol solvent to the ultrapure water in the solvent is analyzed, and the ratio is adjusted and then recycled to step S2. Recovering the solvent by distillation and condensation not only reduces production costs, but also reduces the pollution of the solvent to the environment, thereby achieving green production.
[0056] As a specific example, the volume ratio of the L1 solution to the L2 solution is 5:1; in S3, the dripping rate is 0.5mL / min-10mL / min; and / or the dripping time t is 20min≤t≤180min. The size of the generated SiO2 particles is regulated by regulating the dripping rate: when the dripping rate is faster, the formed SiO2 particles are smaller; when the dripping rate is slower, the formed SiO2 particles are larger; this method is used to control the particle size and uniformity of silica.
[0057] As a specific example, in S4, the concentration of the ammonia water is 0.5 mol / L, the ammonia water is electronic grade ammonia water, and the total amount of metal impurities is less than 10 ppb; and / or the dripping rate of the ammonia water is ≤ 0.5 mL / min. The dripping rate of the ammonia water is controlled to avoid precipitation caused by too fast a dripping rate.
[0058] As a specific example, in S1, the silicon alkoxide is ethyl orthosilicate and / or methyl orthosilicate; the molar ratio of the silicon alkoxide to the alcohol solvent is 1:(10-50).
[0059] As a specific example, in S2, the acid catalyst is one or more of electronic grade hydrochloric acid, nitric acid, and sulfuric acid; the resistivity of the ultrapure water at 25°C is greater than 18MΩ·cm; and the molar ratio of the acid catalyst, alcohol solvent, and ultrapure water is 1:(4-10):(10-20).
[0060] As a specific example, in S1 and S2, the alcohol solvent is anhydrous ethanol or anhydrous methanol.
[0061] As a specific example, before S1, a distillation step of the silicon alkoxide is also included.
[0062] The following are specific embodiments.
[0063] Example 1
[0064] This embodiment relates to a method for preparing synthetic quartz sand by a sol-gel method, comprising the following steps:
[0065] (1) Using tetraethyl orthosilicate as a silicon source, firstly subjecting the tetraethyl orthosilicate to multiple distillations;
[0066] (2) Accurately weigh 0.15 mol of distilled ethyl orthosilicate and 3.75 mol of anhydrous ethanol, mix them, and stir them at 40°C for 30 min to form a homogeneous solution, which is recorded as L1;
[0067] (3) Accurately weigh 0.01 mol of HCl, 0.05 mol of anhydrous ethanol, and 0.15 mol of ultrapure water to prepare a mixed solution, denoted as L2
[0068] (4) At 40°C, add L1 solution into L1 at a rate of 1.0 mL / min (L1:L2 volume ratio 5:1), keeping the temperature constant during the addition process;
[0069] (5) After the addition is complete, stirring is continued at 40°C for 2.5 hours to allow the hydrolysis to proceed. After the reaction is complete, a transparent SiO2 sol is obtained, and its particle size distribution is as follows: Figure 3 As shown, it can be seen that the sol particle size is highly uniform, and the average particle size is about 8 μm;
[0070] (6) preparing a certain amount of 0.5 mol / L electronic grade ammonia solution, slowly adding it dropwise to the transparent sol in step (5) at a dropping speed of 0.5 mL / min, stirring continuously, adjusting the pH to 5.5, and placing it in a vacuum drying oven at 60° C. to stand;
[0071] (7) drying the wet gel obtained in step (6) at 120° C.; during the drying process, using a condensation device to recover and reuse the solvent;
[0072] (8) The dry gel obtained in step (7) is placed in a sintering furnace, heated from room temperature to 300°C and then kept warm for 30 minutes; heated to 500°C and then kept warm for 1 hour; heated to 1100°C and then kept warm for 4 hours, thereby obtaining high-purity synthetic quartz sand. In this embodiment, under the condition of pH 5.5, the dry gel is formed by standing at 60°C for 4 hours, and the dry gel is sintered at 1100°C for 4 hours to obtain synthetic quartz sand with good transparency, such as Figure 4 As shown, the purity of quartz sand reaches 5N8.
[0073] Example 2
[0074] This embodiment relates to a method for preparing synthetic quartz sand by a sol-gel method, comprising the following steps:
[0075] (1) Using tetraethyl orthosilicate as a silicon source, firstly subjecting the tetraethyl orthosilicate to multiple distillations;
[0076] (2) Accurately weigh 0.15 mol of distilled ethyl orthosilicate and 3.75 mol of anhydrous ethanol, mix them, and stir them at 40°C for 30 min to form a homogeneous solution, which is recorded as L1;
[0077] (3) Accurately weigh 0.01 mol of HCl, 0.05 mol of anhydrous ethanol, and 0.15 mol of ultrapure water to prepare a mixed solution, denoted as L2
[0078] (4) At 40°C, add L1 solution into L1 at a rate of 5.0 mL / min (L1:L2 volume ratio 5:1), keeping the temperature constant during the addition process;
[0079] (5) After the addition is complete, stirring is continued at 40°C for 2.5 hours to allow the hydrolysis to proceed. After the reaction is complete, a transparent SiO2 sol is obtained, and its particle size distribution is as follows: Figure 5 As shown, it can be seen that the sol particle size is highly uniform, and the average particle size is about 1.5 μm;
[0080] (6) preparing a certain amount of 0.5 mol / L electronic grade ammonia solution, slowly adding it dropwise to the transparent sol in step (5) at a dropping speed of 0.5 mL / min, stirring continuously, adjusting the pH to 8, and placing it in a vacuum drying oven at 60° C. to stand;
[0081] (7) drying the wet gel obtained in step (6) at 120° C.; during the drying process, using a condensation device to recover and reuse the solvent;
[0082] (8) The dry gel obtained in step (7) is placed in a sintering furnace, heated from room temperature to 300°C and then kept warm for 30 minutes; heated to 500°C and then kept warm for 1 hour, heated to 900°C and then kept warm for 4 hours, thereby obtaining high-purity synthetic quartz sand. In this embodiment, under the condition of pH 8, gel is formed by standing at 60°C for 1 hour, and the dry gel is sintered at 900°C for 4 hours to obtain synthetic quartz sand with good transparency, such as Figure 6 As shown, the purity of quartz sand reaches 6N.
[0083] From the comparison between Example 1 and Example 2, it can be seen that as the pH increases, the gelation time of the sol at 60°C is greatly shortened; increasing the dripping speed of the L1 solution can reduce the sintering temperature. The dry gel SiO2 prepared in Example 2 is kept at 900°C for 4 hours to obtain high-purity synthetic quartz sand with good transparency. This is mainly because when the silicon source dripping speed is slow, the concentration of the silicon source is low at the initial stage of the reaction, which will cause a small number of silica particles to be formed in the reaction system first. As the silicon source continues to drip, the silicate monomer Growth will be continuously added on the surface of these particles (seeds), so that the size of the prepared particles will increase; when the silicon source is added at a faster rate, more small-sized SiO2 particles will be generated in the initial stage of the reaction. As the silicon source continues to be added, the small particles gradually mature and grow slowly, that is, when the drop rate is fast, the sol SiO2 particle size is relatively smaller; the corresponding small-sized SiO2 particles have a large specific surface area and are very active, so the required sintering temperature is relatively low. Therefore, the small-sized SiO2 particles in Example 2 can be sintered at only 900°C to prepare highly transparent quartz sand.
[0084] Comparative Example 1
[0085] The difference between this comparative example and Example 1 is that in step (4), the L1 solution is directly added to the L2 solution by pouring, and the other steps and parameters remain unchanged. In step (6) of this comparative example, under the condition of pH 5.5, the gel is formed after standing at 60°C for 15 hours, and the gel time is greatly increased. At the same time, the quartz sand prepared in this comparative example is shown in the picture Figure 7 As shown, the purity of the quartz sand is only 4N. This is because the L1 solution is added too quickly, so that the silicon source cannot be completely hydrolyzed, and some unhydrolyzed silicon source remains, resulting in reduced purity.
[0086] Comparative Example 2
[0087] The difference between this comparative example and Example 1 is that in step (6), no ammonia water is added to adjust the pH, and the sol prepared in step (5) is directly placed at 60°C for 18 hours, and the other steps and parameters remain unchanged. In step (6) of this comparative example, the gel is formed after being placed at 60°C for 18 hours, and the gel time is greatly increased. At the same time, the quartz sand prepared in this comparative example is shown in the picture Figure 8 As shown, synthetic quartz sand still has unsintered transparent particles, such as Figure 8 The particles are framed.
[0088] Comparative Example 3
[0089] The difference between this comparative example and Example 1 is that in step (6), ammonia water is added by direct pouring to adjust the pH, and then placed at 60°C for standing, and other steps and parameters remain unchanged. In this comparative example, ammonia water is added by pouring at one time. Due to the high concentration of ammonia water in the local area, a precipitate is formed, and gel cannot be formed at 60°C. After the precipitate is dried, it is kept at 1100°C for 4 hours. The synthetic quartz sand obtained is as follows Fig. 9 As shown, it can be seen that the synthetic quartz sand prepared by this method cannot be sintered to be transparent.
[0090] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing synthetic quartz sand by a sol-gel method, characterized in that: The steps include: S1, mixing silicon alkoxide and alcohol solvent, stirring at 40-60°C to form a homogeneous solution, recorded as L1; S2, mixing the acidic catalyst, the alcohol solvent and the ultrapure water to form a mixed solution, recorded as L2; S3, at 40-60°C, add L1 solution to L2 solution, then continue stirring and hydrolyzing to obtain SiO2 sol; S4, under stirring, adding ammonia water dropwise to the SiO2 sol until the pH value is 5-10, and placing the sol in a vacuum drying oven at 60-80° C. to obtain a wet gel; S5, drying the wet gel, and then placing it in a sintering furnace for sintering to obtain high-purity synthetic quartz sand.
2. The method for preparing synthetic quartz sand by the sol-gel method according to claim 1, characterized in that: In S5, the sintering treatment conditions are: heating from room temperature to 300°C and keeping it for 10-30 minutes, heating to 500°C and keeping it for 30-60 minutes, and then heating to 900-1100°C and keeping it for 240-300 minutes.
3. The method for preparing synthetic quartz sand by the sol-gel method according to claim 1, characterized in that: In S5, the drying process is carried out by heating in an oil bath, and the temperature of the drying process is 120-150°C.
4. The method for preparing synthetic quartz sand by a sol-gel method as claimed in claim 1, characterized in that: In S5, during the drying process, a condensing device is used to recover the solvent, wherein the solvent includes an alcohol solvent and ultrapure water, and the ratio of the alcohol solvent to the ultrapure water in the solvent is analyzed, and the ratio is adjusted and then recycled to step S2.
5. The method for preparing synthetic quartz sand by the sol-gel method according to claim 1, characterized in that: The volume ratio of the L1 solution to the L2 solution is 5:1; In S3, the dropping rate is 0.5 mL / min-10 mL / min; and / or the dropping time t is 20 min≤t≤180 min.
6. The method for preparing synthetic quartz sand by the sol-gel method according to claim 1, characterized in that: In S4, the concentration of the ammonia water is 0.5 mol / L, the ammonia water is electronic grade ammonia water, and the total amount of metal impurities is less than 10 ppb; And / or, the dropping rate of the ammonia water is ≤0.5 mL / min.
7. The method for preparing synthetic quartz sand by a sol-gel method as claimed in claim 1, characterized in that: In S1, the silicon alkoxide is ethyl orthosilicate and / or methyl orthosilicate; And / or, the molar ratio of the silicon alkoxide to the alcohol solvent is 1:(10-50).
8. The method for preparing synthetic quartz sand by the sol-gel method according to claim 1, characterized in that: In S2, the acidic catalyst is one or more of electronic grade hydrochloric acid, nitric acid, and sulfuric acid; And / or, the resistivity of the ultrapure water at 25° C. is greater than 18 MΩ·cm; And / or, the molar ratio of the acidic catalyst, the alcohol solvent and the ultrapure water is 1:(4-10):(10-20).
9. The method for preparing synthetic quartz sand by a sol-gel method as claimed in claim 1, characterized in that: In S1 and S2, the alcohol solvent is anhydrous ethanol or anhydrous methanol.
10. The method for preparing synthetic quartz sand by the sol-gel method according to claim 1, characterized in that: Before S1, a distillation step of the silicon alkoxide is also included.
Citation Information
Cited By
Preparation method of high-purity synthetic quartz sand
CN120829163A
Sintering method for preparing high-density synthetic sand
CN121823949A
Method for preparing low-carbon synthetic quartz sand from natural quartz graded fine sand
CN121948475A